The Use of Ice Breaking in The Jigsaw Cooperative Learning Model to Increase Learning Motivation of Fourth-Grade Students of SD Inpres 2 Tondo - Nur Salsa Aurelya; Abdul Rahman; Nuraini Nuraini; Azizah Azizah; Sukri Sukri (FKIP - Universitas Riau, 2026)
Learning motivation is critical in elementary education, yet monotonous classroom activities often result in low student engagement. This study examined the effect of integrating ice breaking into the Jigsaw cooperative learning model on fourth-grade students' learning motivation. Using a quasi-experimental design with nonequivalent control groups, 38 students from SD Inpres 2 Tondo were divided into experimental (n=19) and control (n=19) groups. Data were collected through validated questionnaires (Cronbach's α=0.689), observation sheets, and documentation, analyzed using descriptive statistics, N-Gain, Wilcoxon Signed-Rank, and Mann-Whitney U tests. Results showed the experimental group improved from pretest mean 33.63 to posttest 53.53 (N-Gain=0.296, moderate), while the control group increased from 26.37 to 45.95 (N-Gain=0.262, low). Wilcoxon and Mann-Whitney tests confirmed significant differences (p<0.05). Observations revealed higher motivation in the experimental class (73.94%) versus control (70.23%). This study concludes that ice breaking integrated with Jigsaw significantly enhances elementary students' learning motivation.